Shared genetic architecture of gastroesophageal reflux disease and age related phenotypes - Wei Liu; Yadan Xiao; Manting Zeng (Scientific Reports)
Abstract Increasing age is a risk factor of gastroesophageal reflux disease. This study aims to uncover the shared genetic architecture of gastroesophageal reflux disease (GERD) and age-related phenotypes. Based on publicly available GWAS statistics, this genome-wide pleiotropic association research was performed with multiple genetic approaches sequentially to explore the pleiotropic associations from single-nucleotide polymorphism (SNP) and gene levels, to reveal the underlying shared genetic etiology between GERD and age-related phenotypes. This study featured shared genetic mechanisms between GERD and age-related phenotypes, including frailty index (FI), telomere length (TL), longevity, and parental lifespan (PL). Strong genetic association were observed. A set of pleiotropic loci and genes were identified by PLACO, FUMA, Bayesian colocalization and additional MAGMA analysis. Our research provided strong evidence of genetic correlation between GERD and several age-related phenotypes, especially frailty index (FI) and telomere length (TL), brought novel insight into the shared genetic architecture between GERD and aging.